Solvent-free carbon sphere nanofluids towards intelligent lubrication regulation - Sheng Zhang; Wen Li; Xiaoliang Ma; Xiaoqiang Fan; Minhao Zhu (Friction)
Abstract By simply switching the electrical circuit installed on steel/steel contact, the tribological behaviors of nanofluids (NFs) can be regulated in real time, thereby achieving the desired performance of friction reduction and wear resistance. Herein, solvent-free carbon spherical nanofluids (C-NFs) were successfully prepared for intelligent lubrication regulation. C-NFs with excellent lubrication performance can immediately reduce the coefficient of friction (COF) despite applying a weak electric potential (1.5 V). Moreover, polyethylene glycol 400 (PEG400) containing 5.0 wt% C-NFs remained responsive to electrical stimulation under the intermittent voltage application with an average coefficient of friction (ACOF) reduction of 20.8% over PEG400. Such intelligent lubrication regulation of C-NFs under an external electric field (EEF) mainly depends on the orderly arranged double-electric adsorption film of ion canopy-adsorbed carbon spheres (CSs). The intermittent electrical application can continuously reinforce the adsorption film and its durability for real-time controlling the sliding interfaces. Electrical-stimulation-responsive intelligent lubricants provide a new technical support for realizing intelligent stepless control of devices.